Evaluation of an inter-professional training program for student clinical supervision in Australia - Gillieatt, Sue; Martin, Robyn; Marchant, Trudi; Fielding, Angela; Duncanson, Kate (BioMed Central Ltd, 2014)
Background: As a response to an Australian shortage of clinical health, nursing, and medical placements, Commonwealth Government funding has been directed to expand student training opportunities and increase the competence and number of available clinical supervisors. This paper evaluates the application of a particular supervision training model for this purpose. It considers the model's suitability and relevance across professions and its impact on supervisory knowledge, skills, and values as well as the intention to supervise students. Methods: The design, delivery, and evaluation of a series of one-day introductory student clinical supervision training workshops for allied health disciplines, nursing, and medicine are considered. Participants evaluated Proctor's model of clinical supervision, which was expanded by the trainers to incorporate diversity and power relations in student supervision. Results: Evaluation results suggest that adapting Proctor's model for student clinical supervision is relevant across a broad range of health disciplines and clinical areas. Participants from 11 health professions reported that the training improved their knowledge, skills, and values and expanded their willingness to accept student clinical placements. The outcomes are suggestive of enhanced clinical supervision intent, capacity, and capability. Conclusions: The student supervision training improved participants' confidence in their clinical supervision skills. The findings suggest that the training has the potential to extend capacity and capability for student supervision across health professions and in Health Workforce Australia's identified priority areas of mental health, community health, rehabilitation, private practice, and non-government organisations. Findings also indicate that these gains are reliant on health organizations developing and sustaining cultures of learning.